2017
DOI: 10.1007/s10103-017-2401-9
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin sulfate and glucosamine sulfate associated to photobiomodulation prevents degenerative morphological changes in an experimental model of osteoarthritis in rats

Abstract: The aim of this study was to compare the effects of combined treatment with chondroitin sulfate and glucosamine sulfate (CS/Gl) and photobiomodulation (PBM) on the degenerative process related to osteoarthritis (OA) in the articular cartilage in rats. Forty male Wistar rats were randomly divided into four groups: OA control group (CG); OA animals submitted to PBM treatment (PBM); OA animals submitted to CS/Gl treatment (CS/Gl); OA submitted to CS/GS associated with PBM treatments (GS/Gl + PBM). The CS/Gl start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
1
25
0
2
Order By: Relevance
“…Additionally, male Wistar rats with surgically induced OA were treated with glucosamine sulphate (500 mg/kg) and chondroitin sulphate for 1 month. Similar to the findings of Li et al, these treated OA rats showed substantial improvement in joint histology grading with reduced IL-1β expression relative to the negative controls [55].…”
Section: Anti-inflammatory Activities Of Glucosaminesupporting
confidence: 84%
See 2 more Smart Citations
“…Additionally, male Wistar rats with surgically induced OA were treated with glucosamine sulphate (500 mg/kg) and chondroitin sulphate for 1 month. Similar to the findings of Li et al, these treated OA rats showed substantial improvement in joint histology grading with reduced IL-1β expression relative to the negative controls [55].…”
Section: Anti-inflammatory Activities Of Glucosaminesupporting
confidence: 84%
“…Considering the role of inflammation in OA, an anti-inflammatory agent should be beneficial in slowing down the progression of this disease [50,51]. Numerous animal [52][53][54][55] and human [56] studies reported that glucosamine possesses anti-inflammatory activities in OA. Aghazadeh-Habashi et al analyzed the effects of different doses of glucosamine (20,40,80, or 160 mg/kg/day) on rats with and found that 6-day glucosamine supplementation reduced the levels of proinflammatory cytokines IL-1, IL-6, and TNF-α and prevented the increase in the serum concentrations of nitrite, a stable metabolite of NO in rats with OA [52].…”
Section: Anti-inflammatory Activities Of Glucosaminementioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, 10% of people older than 60 years are estimated to manifest OA symptoms [1]. Furthermore, OA has been shown to be associated with aging, being overweight or obese, cartilage injuries, and genetic factors [2][3][4]. Mechanical stress-induced inflammation plays an important role in OA.…”
Section: Introductionmentioning
confidence: 99%
“…Chondroitin sulfate (CS) is one of the main GAGs that can be found in cartilage. CS helps chondrocytes entrench to ECM by its mechanical properties …”
Section: Introductionmentioning
confidence: 99%